2019
DOI: 10.5334/aogh.2437
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Colorectal Cancer and Attitudes Towards Its Screening Guidelines in Lebanon

Abstract: Background: Screening for colorectal cancer (CRC) provides an effective strategy for early detection and prevention of the disease; however, global screening rates are still low. Purpose: This study aims at assessing the awareness of CRC risk factors, warning signs, and attitudes towards CRC guidelines and screening modalities, in order to identify the barriers to and correlates of CRC screening in the Lebanese population. Methods: A self-adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
79
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 30 publications
21
79
7
Order By: Relevance
“…One of the reasons for the high incidence rate of this disease is the air pollution and stress of living in some of the cities in these regions. On the other hand, modernization of the country, which is more prominent in larger cities, not only has changed dietary habits but also has led to cultural shifts, such as the increase in the age of marriage and age at first birth, which are common risk factors for breast cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for the high incidence rate of this disease is the air pollution and stress of living in some of the cities in these regions. On the other hand, modernization of the country, which is more prominent in larger cities, not only has changed dietary habits but also has led to cultural shifts, such as the increase in the age of marriage and age at first birth, which are common risk factors for breast cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of an effective colorectal cancer screening program has the potential to make a significant impact on the burden of disease as many colorectal cancers are curable if detected early and preventable if excised at the pre-malignant stage [ 5 , 6 ]. Unfortunately, nationwide cancer screening efforts remain a significant challenge in Ghana, even with more prevalent diseases such as prostate, breast and cervical cancers [ 3 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that age, smoking and BMI were the most important risk factors for the detection of AN. These are well established risk factors that have been used in many models of colon cancer risk with biological plausibility previously explored[ 15 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the second highest incidence rate of colorectal cancer in the Middle East and North Africa (MENA) region[ 14 ]. No formal study has evaluated the percentage of age-eligible patients who have received colorectal cancer screening, but one study reported a rate of 15% in an inpatient cohort aged 25 and older[ 15 ]. This makes improved enrollment in screening programs and the subsequent detection of adenomas and AN of crucial importance in Lebanon and similar regions where no national screening programs have been formally implemented.…”
Section: Introductionmentioning
confidence: 99%